The Effects of Emotional Visual Context on the Encoding and Retrieval of Body Odor Information. (April 2018) - Parma, Valentina; Macedo, Stephanie; Rocha, Marta; Alho, Laura; Ferreira, Jacqueline; Soares, Sandra C.
Conditions during information encoding and retrieval are known to influence the sensory material stored and its recapitulation. However, little is known about such processes in olfaction. Here, we capitalized on the uniqueness of body odors (BOs) which, similar to fingerprints, allow for the identification of a specific person, by associating their presentation to a negative or a neutral emotional context. One hundred twenty-five receivers (68 F) were exposed to a male BO while watching either criminal or neutral videos (encoding phase) and were subsequently asked to recognize the target BO within either a congruent or an incongruent visual context (retrieval phase). The results showed that criminal videos were rated as more vivid, unpleasant, and arousing than neutral videos both at encoding and retrieval. Moreover, in terms of BO ratings, we found that odor intensity and arousal allow to distinguish the target from the foils when congruent criminal information is presented at encoding and retrieval. Finally, the accuracy performance was not significantly different from chance level for either condition. These findings provide insights on how olfactory memories are processed in emotional situations.